(untitled) (The Geographic Base, 2024)
Nepal is characterized by remarkable physiographic diversity, which poses highly productive agricultural land across its southern plains stretching from east to west. However, limited precipitation and a declining trend in agricultural productivity has made accurate evapotranspiration (ET) estimation increasingly important, particularly during the dry season. This study presents an alternative approach the temperature-vegetation index T-VI space method for estimating ET with higher accuracy compared to previous studies that used different techniques. The root mean square error (RMSE) and mean absolute percentage error (MAPE) for daily ET (hourly ET) were 0.469 mm d-1 (0.09 mm h-1) and 15.29% (15.45%) respectively. The high-resolution ET estimates (30m) obtained in this research, demonstrate that the T-VI space method is applicable in Nepal, providing valuable insights into regional hydrological processes, water stress patterns, and drought conditions within a single analytical framework. The findings offer practical benefits for local farmers and government agencies for supporting future agricultural planning and promoting the efficient use of irrigation water.